Cytoglobin is upregulated by tumour hypoxia and silenced by promoter hypermethylation in head and neck cancer - Okonjo, FA; Shaw, RJ; Omar, MM; Rokadiya, S; Lowe, D; Hall, GL; Woolgar, JA; Homer, J; Liloglou, T; Field, JK; Risk, JM (Springer Nature, 2009)
Background: Cytoglobin (Cygb) was first described in 2002 as an intracellular globin of unknown function. We have previously shown the downregulation of cytoglobin as a key event in a familial cancer syndrome of the upper aerodigestive tract.